Changes in performance markers and wellbeing in elite senior professional rugby union players during a pre-season period: Analysis of the differences across training phases - Grainger, A.; Neville, R.; Ditroilo, M.; Comfort, P. (Journal of Science and Medicine in Sport, 2020)
Objectives: To assess the magnitude of change and association with variation in training load of two performance markers and wellbeing, over three pre-season training blocks, in elite rugby union athletes. Design: Observational. Methods: Twenty-two professional players (age 25 ± 5 years; training age 6 ± 5 years; body mass, 99 ± 13 kg; stature 186 ± 6 cm) participated in this study, with changes in lower (CMJ height) and upper body (bench press mean speed) neuromuscular function and self-reported wellbeing (WB) assessed during an 11-week period. Results: There was a small increase in CMJ height (0.27, ±0.17 - likely substantial; standardised effect size, ±95% confidence limits - magnitude-based inference) (p = 0.003), bench press speed (0.26, ±0.15 - likely substantial) (p = 0.001) and WB (0.26, ±0.12 - possibly substantial) (p < 0.0001) across the pre-season period. There was a substantial interaction in the effect of training load on these three variables across the three training phases. A two-standard deviation (2SD) change in training load was associated with: a small decrease in CMJ height during the power phase (-0.32, ±0.19 - likely substantial) (p = 0.001); a small reduction in bench press speed during the hypertrophy phase (-0.40, ±0.32 - likely substantial) (p = 0.02); and a small reduction in WB during the strength phase (-0.40, ±0.24 - very likely substantial) (p < 0.0001). The effects of changes in training load across other phases were either likely trivial, only possibly substantial, or unclear. Conclusions: The effect of training load on performance can vary both according to the type of training stimulus being administered and based on whether upper- or lower-body outcomes are being measured.